Innovative Technologies in Teaching Examples of Folk Art in Primary School "Mother Tongue and Reading Literacy" Lessons - Ruzikulova Nigora Kudratovna; M. Y. Roziyeva (International Journal on Integrated Education, 2023)
This article presents analytical examples of the role of folklore in primary classes, the effective use of folklore genres, proverbs, fairy tales, riddles, narrative genres.